Perception of Speech Acts Categories in Donald Trump’s Tweets by Native and Nonnative Speakers of English - Souri, Davood; Merç, Ali (Language Circle: Journal of Language and Literature, 2020)
Twitter plays an important role in today’s world. Its role among politicians and those who are interested in politics is more obvious. Due to its importance and special characteristics such as character limits, it has drawn the attention of many researchers including linguists and ELT researchers. This study aimed to compare the perceptions of native and nonnative speakers in identifying speech acts in Donald Trump’s tweets. The subjects of this study were nine English native speakers and twenty nonnative English teachers who were Turkish citizens. Thirty- seven tweets of Donald Trump over the course of a week were selected and the participants were asked to identify the speech acts of the tweets based on the speech acts taxonomy by Searle (1976). The analysis of the data revealed that both native and nonnative speakers of English identified the speech acts of the large majority of the tweets very differently. These differences were partly due to lack of enough political as well as background knowledge and partly due to lack of contextual variables.